PARAMETER PENENTU AKSESIBILITAS PENGUNJUNG WISATA PANTAI KOKA DI DESA WOLOWIRO KECAMATAN PAGA KABUPATEN SIKKA PROVINSI NTT - Alfridus Gado; Mansuetus Gare (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
The Sikka Regency area is one of the areas located on the island of Flores, East Nusa Tenggara Province. The region has a lot of interesting natural and cultural wealth, but there are still many hidden due to the lack of infrastructure development. One of the natural wealth is the Koka beach tourist attraction which is a tourist attraction located in Wolowiro village, Paga district, Sikka regency. The construction of road infrastructure for Koka Beach tourism is inadequate, there is one point that has not been paved and there are several points that are still damaged due to land disputes between the village government and the landowner. The focus of this study is to analyze the parameters that affect the accessibility of coca beach tourism visitors in Wolowiro Village, Paga District, Sikka Regency, East Nusa Tenggara Province which are adapted to existing conditions and their problems using qualitative descriptive analysis methods. Data collection is carried out by observation, interviews, questionnaires, and documentation. Data analysis using Miles and Huberman which includes data reduction, data presentation, and conclusion drawing/verification. The results of this study are in the form of parameters that affect the accessibility of Koka beach tourist visitors, namely the parameters of entrance rates, road infrastructure conditions, Koka beach tourist attraction facilities, and the behavior of the management of coca beach tourist attractions affecting the accessibility of Koka beach tourist visitors to be hampered. Suggestions that can be given to local governments need to be carried out development of supporting facilities and infrastructure in coca beach tourist attractions and for further studies, quantitative methods are used so that quantitative methods can be measured and described in detail about the parameters that affect the accessibility of coca beach tourist visitors.